2014
DOI: 10.3392/sociotechnica.11.119
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phosphorus Dependency in Asia

Abstract: The BACI trade statistics for 2005 were analyzed to determine the dependency of Asian countries on phosphorus, in particular for phosphorus ore, yellow phosphorus, chemicals, and fertilizers. The data revealed a complex set of patterns, with some countries relying heavily on just one or two countries to meet their commodity needs, and others drawing from a wide range of sources. In many cases, a strong dependency was noted on a country which itself was heavily dependent on another source for its commodity need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Global demand for P fertilizer is increasing continuously, whereas global commercial phosphate reserves are estimated to be depleted within a few decades 3 , 4 and no known substitute for P is available presently 5 , 6 . In India, the soils are either low (49.3% of soils) or medium (48.8% of soils) in terms of available P 7 , 8 and this necessitates the country to import the phosphorus-based fertilizers in a larger scale with 90% dependency 9 , 10 . It is therefore imperative that one should be ready with alternative solutions for this problem, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Global demand for P fertilizer is increasing continuously, whereas global commercial phosphate reserves are estimated to be depleted within a few decades 3 , 4 and no known substitute for P is available presently 5 , 6 . In India, the soils are either low (49.3% of soils) or medium (48.8% of soils) in terms of available P 7 , 8 and this necessitates the country to import the phosphorus-based fertilizers in a larger scale with 90% dependency 9 , 10 . It is therefore imperative that one should be ready with alternative solutions for this problem, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To meet their national demand for P resources, Asian countries tend to be heavily dependent on imports [47,48]. Smit et al (2015) [14] reported that the import of fertilizer was decreasing but that the import of food and feed additives was increasing.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…Population growth, rural-urban migration and urbanization were the main drivers for the higher P footprint in China [32,35,46]. Along with urbanization, population growth and economic growth have been reported as the dominant factors expected to result in a higher P demand over time in Asia [47,48].…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…If we suppose that that phosphorus rock has a P2O5 of 30%, the hidden phosphorus flow from the steelmaking process was equivalent to 2% of the global phosphorus supply in 1980 and 4% in 2013. It is worth noting that the hidden phosphorus flow in China was more than 500 kt-P, more than 10 times the amount of phosphate rock exported by China in 2013 (BACI, 2013;Webeck, 2014a).…”
Section: Estimationmentioning
confidence: 99%